Panorama artístico no século XVIII dos conventos franciscanos femininos em Braga : tópicos para uma abordagem - Rocha, Manuel Joaquim Moreira da (2009)
D. Rodrigo de Moura Teles, archbishop of Braga from 1704 to 1728, was responsible for promoting the foundation of female Franciscan convents, and instituted three buildings for religious communities in the towns of Braga, Guimarães and Chaves, in addition to two other Franciscan convents located in Braga: the 16th-century Convent of Nossa Senhora dos Remédios and the Convent of Nossa Senhora da Conceição dated from the early 17th century. This paper describes the correlation between the bishop's patronage and his clear support to the Franciscan cause and religious art associated to these monasteries. It analyses the artists' profiles, their work and the key elements that help to interpret the monasteries' artistic production and, as a result, describe the character of this patron of the arts.